2018
DOI: 10.3389/fmicb.2017.02688
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Proteins AmiA, AliA, and AliB Bind Peptides Found in Ribosomal Proteins of Other Bacterial Species

Abstract: The nasopharynx is frequently colonized by both commensal and pathogenic bacteria including Streptococcus pneumoniae (pneumococcus). Pneumococcus is an important pathogen responsible for bacterial meningitis and community acquired pneumonia but is also commonly an asymptomatic colonizer of the nasopharynx. Understanding interactions between microbes may provide insights into pathogenesis. Here, we investigated the ability of the three oligopeptide-binding proteins AmiA, AliA, and AliB of an ATP-binding cassett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 29 publications
7
33
0
Order By: Relevance
“…Less suppression of growth was seen by AmiA peptide in the ΔAmiA mutant supporting the idea that this is the specific receptor for the peptide (Figure 1E). In contrast, AliA peptide affects the ΔAliA mutant in the same way as it affects the D39 wild type as expected since AliA peptide is known to bind to AmiA receptor (Figure 1F; Nasher et al, 2018b). Unlike the wild type D39 strain, growth of the D39 ΔAliB mutant was reduced by the AliB peptide (Figure 1G).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Less suppression of growth was seen by AmiA peptide in the ΔAmiA mutant supporting the idea that this is the specific receptor for the peptide (Figure 1E). In contrast, AliA peptide affects the ΔAliA mutant in the same way as it affects the D39 wild type as expected since AliA peptide is known to bind to AmiA receptor (Figure 1F; Nasher et al, 2018b). Unlike the wild type D39 strain, growth of the D39 ΔAliB mutant was reduced by the AliB peptide (Figure 1G).…”
Section: Resultssupporting
confidence: 67%
“…We propose that there is interspecies communication between bacteria that live in the human nasopharynx and that detecting other bacterial species allows S. pneumoniae to adapt to its environment. Previously, we reported that S. pneumoniae AmiA, AliA, and AliB lipoproteins of an ABC transporter are able to bind peptides matching ribosomal proteins of other bacteria species including common nasopharynx colonisers (Nasher et al, 2018b). These proteins are encoded by genes of the core pneumococcal genome (Obert et al, 2006) and so are of relevance across the pneumococcal population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, AliA has been shown to be important for survival in vivo and is thought to play a role in bacterial communication by binding oligopeptides derived from other common colonizers. Peptide uptake by pneumococci via AliA has shown to influence the behavior of the bacterium in vitro, including reduced growth, reduced capsule thickness, and increased biofilm formation [11,57,58,77]. It is, therefore, tempting to speculate that in vivo anti-AliA antibodies could hamper the uptake of oligopeptides by AliA and consequently affect pneumococcal persistence in the host.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pneumoniae (S. pneumoniae) (pneumococcus) is a common asymptomatic colonizer of the human nasopharynx. The human nasopharynx is an ecosystem that hosts a diverse microbial community and we have previously proposed that pneumococcus senses bacteria in the environment through short peptide fragments derived from these other bacterial species sharing the same niche (Hathaway et al, 2014; Nasher et al, 2018a,b).…”
Section: Introductionmentioning
confidence: 99%